Legal Due To The Business Fields Of The Limited Company That Are Not Integrated With Online Single Submission - Syarifah Fitri Sarah; Teuku Ahmad Yani; Yusri Yusri (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Limited Liability Company is the most popular form of business. To run a Limited Liability Company, a clear line of business is needed. The list of business fields in the company is now based on the standard classification of Indonesian business fields or KBLI 2020, because companies that previously used the 2015 KBLI had to adjust the Articles of Association first and the articles of association were notified to the Minister of Law and Human Rights through a notary using the AHU Online application. AHU Online is an electronic-based legal service organized by the Directorate General of General Legal Administration and has been integrated with the Online Single Submission or OSS which is an electronic licensing service. However, it turns out that there are business fields that have been registered with online AHU that are not integrated with OSS. This type of research is empirical juridical, with a legal approach (sculpture approach), and a conceptual approach (conceptual approach). The legal materials used in this study consist of primary, secondary, and tertiary legal materials. The location of this research is in the city of Banda Aceh. The results of the study indicate that the legal consequences of a business field that is not integrated with OSS is that the business field cannot be run, because it cannot obtain a business license, so the company cannot run a business, which fulfills the absolute requirements that must be met to carry out business activities